PdAgAu alloy with high resistance to corrosion by H2S - Braun, Fernando (2012)
PdAgAu alloy films were prepared on porous stainless steel supports by sequential electroless deposition. Two specific compositions, Pd83Ag2Au15 and Pd74Ag14Au12, were studied for their sulfur tolerance. The alloys and a reference Pd foil were exposed to 1000H2S/H2 at 623 K for periods of 3 and 30 h. The microstructure, morphology and bulk composition of both non-exposed and H2S-exposed samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). XRD and SEM analysis revealed time-dependent growth of a bulk Pd4S phase on the Pd foil during H2S exposure. In contrast, the PdAgAu ternary alloys displayed the same FCC structure before and after H2S exposure. In agreement with the XRD and SEM results, sulfur was not detected in the bulk of either ternary alloy samples by EDS, even after 30 h of H2S exposure. X-ray photoelectron spectroscopy (XPS) depth profiles were acquired for both PdAgAu alloys after 3 and 30 h of exposure to characterize sulfur contamination near their surfaces. Very low S 2p and S 2s XPS signals were observed at the top-surfaces of the PdAgAu alloys, and those signals disappeared before the etch depth reached ∼10 nm, even for samples exposed to H2S for 30 h. The depth profile analyses also revealed silver and gold segregation to the surface of the alloys; preferential location of Au on the alloys surface may be related to their resistance to bulk sulfide formation. In preliminary tests, a PdAgAu alloy membrane displayed higher initial H2 permeability than a similarly prepared pure Pd sample and, consistent with resistance to bulk sulfide formation, lower permeability loss in H2S than pure Pd.